Descobrindo as razões trigonométricas no triângulo retângulo - Oliveira, Henrique (2013)
One of the important consequences of trigonometry is the ratio that exists between sides of similar triangles. Such reason appears frequently in many everyday problems and can be quite explored in the classroom. The aim of this study was to explore the trigonometric ratio in the right triangle. The working hypothesis was that the ratios between sides are constant. So the approach was carried out in two ways: one using ruler and protractor and the other with the free software of dynamic geometry called Geogebra. The proposed activities were implemented in a classroom of the 3rd year of high school in the city of Franca, São Paulo State and the Didactic Engineering was used as a research methodology. In both steps of the implementation of the project the expected results have been achieved successfully, however, in the second stage, the use of the software was a motivator of the activity, not only facilitating the visualization of buildings, but also providing the exact value of the reason. Throughout the project implementation a number of other themes could be explored, such as the metric system and the error in the approximations. The use of information technology in the classroom contributed so that classes would be more dynamic and the students more motivated. It is hoped that the material presented here may be useful for other teachers employ in their classes or tailor it to other contents. It is expected that this work will stimulate other teachers to use the technological resources as tools to support teaching.